THE EFFECTIVENESS OF THE LEARNING AND MINI-RESEARCH INTEGRATION PROGRAM IN IMPROVING THE QUALITY OF ISLAMIC EDUCATION: A STUDY AT THE ISLAMIC EDUCATION MANAGEMENT STUDY PROGRAM OF STAI DARUSSALAM KUNIR - Ahmad Farihin; Singgih Aji Purnomo; Ferianto Ferianto (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study analyzes the effectiveness of the Learning and Mini-Research Integration Program in improving the quality of Islamic education in the Islamic Education Management Study Program of STAI Darussalam Kunir. It focuses on research management, program implementation, and supporting and inhibiting factors. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation from LPPM, study program leaders, students, staff, and partner school principals, then analyzed through reduction, display, and verification with triangulation and member checking.The results show that the program is quite effective. Research management is conducted through structured planning, organizing, implementation, and evaluation. The integration of learning and mini-research creates more contextual learning by linking theory with field data. The program also improves students’ research skills, supports lecturers’ tridharma, strengthens academic culture, and benefits partner institutions. The main obstacle is students’ limited research competence, but this is supported by institutional policies, lecturer involvement, and partner networks.In conclusion, the program is an effective strategy to enhance the quality of Islamic education through research-based learning, improved student competence, and strengthened academic culture.